Aplikasi Teknologi Realiti Teknologi Realiti Maya Dalam E-Pembelajaran Untuk Mata Pelajaran Teknologi Maklumat KBSM - Pajuzi, Awang (2002)

(untitled)
In education field, applications of Virtual Reality (VR) technology is designed to fulfill of training and simulation due to the importance and needs to use the 3D elements and 360" degrees panorama for educational purposes. Virtual Reality technology could be used as an educational tool to help student gain understanding of complex system and processes and abstract model. Applications Virtual Reality Technology in e-learning for Information Technology subject in KBSM consists of two main parts. First part, the development software prototype for teaching and learning process of Information Technology under the topic of Computer System. The second part on the other hand covers the testing process on software prototype. Model ADDIE consists Analysis, Design, Development, Implementation and Evaluation is the system methodology used in the study. For this purposes a study has been carried out of hundred students from Sekolah Menengah Sains Pokok Sena Kedah and Sekolah Menengah Sultan Abdul Halim Jitra Kedah. Particularly, based on reseach findings, there have three principal advantages of VR in education i.e improving spatial thinking, increasing interest level and promoting individualized learning for students.